Genotype x environment interaction and stability analysis of grain sorghum (Sorghum bicolor (L.) Moench) yield under rainfed and irrigation conditions in central Sudan - Mohammed, Mohammed; Ibrahim, Abu Elhassan; Elzein., Ibrahim (Gezira Journal of Agricultural Science; Vol 13 No 2 (2015), 2015)
An experiment was conducted over three consecutive seasons (2009, 2010, and 2011) at three locations , Rahad Research farm. Gedarif  Research Station farm (North Gedarif and South Gedarif region) of the Agricultural Research Corporation (ARC), Sudan. Both North and South Gedarif were rainfed, while Rahad station was irrigated. A randomized complete block design with four replicates was used. Sorghum production is highly influenced by the environment where it is grown, thus, the genotype by environment interaction is highly significant when breeding for specific adaptation. The objective was   to assess the genotype x environment interaction and stability of grain yield. The mean squares due to environment, genotypes and genotype x environment interaction were highly significant for grain yield. Significant differences among  genotypes for the studied characters were found in almost all seasons, indicating that these sorghum genotypes were highly variable for the characters studied and , therefore, expected to respond to selection. The interaction effects of genotype x location were highly significant for most traits indicating that genotypes responded differently to different environments and some are environmentally specific. The present study showed that the first two axes PCA1,PCA2 in Additive Main Effect and Multiplicative Interaction (AMMI ) accounted for the GE sum of squares by 56.7% and 19.3%, respectively, while the regression analysis accounted for GE sum of squares by 21.9% .Hence, AMMI analysis was superior to regression techniques and more effective in partitioning the interaction sum of squares. From both statistical  stability models used in this study, i.e. Eberhart and Russell (1966) as well as the Aditive Main Effect and Multiplicative Interaction (AMMI) analysis, they pointed out  that genotypes Mugod (1510 kg/ha), Tabat (1299 kg/ha), Wad-Ahmed (1471 kg/ha), Gadambalia bloom (1428 kg/ha), Safra (1410 kg/ha) and Tetron (1323) were high yielding and stable under the favorable environments of South Gedarif and Rahad irrigated Scheme. Genotypes Wad Baku(1225 kg/ha), Farhoda (1252 kg/ha),Gesheish (1194 kg/ha) and Wad Fahal (1230 kg/ha) were low yielders but quite stable under low rainfall environments like North Gedarif environment         أجريت هذه التجربة  لثلاث مواسم متتالية ( 2009 ، 2010 و 2011 ) وفي ثلاثة مواقع هي مزرعة بحوث الرهد ومحطة بحوث القضارف ( منطقة شمال وجنوب القضارف) ،هيئة البحوث الزراعية، السودان، واللتان تمت فيهما الزراعة بالأمطار ، أما محطة الرهد بالري الانسيابي. استخدم تصميم القطاعات العشوائية الكاملة بأربعه مكررات. وجد أن البيئة لها تأثير كبير علي انتاجية الذرة الرفيعة في مناطق زراعتها وعلية فأن التفاعل الوراثي والبيئي عالي المعنوية في حالة التربية لبيئات محددة. هدفت الدراسة لتقويم التفاعل الوراثي والبيئي وثبات درجة انتاجية الحبوب في الذرة. أظهرت النتائج وجود فروق معنوية عالية للبيئات ‚الأصناف والتفاعل الوراثي والبيئي. أيضاً أظهرت الدراسة فروقات معنوية عالية لمعظم الصفات التي درست في كل المواسم ، وهذا يشير الى وجود فروقات عالية بين سلالات الذرة للصفات التي درست ، وعليه يمكنها الاستجابة للانتخاب . التفاعل الوراثي والبيئي به فروق معنوية لمعظم الصفات وهذا يوضح أن هذه السلالات تختلف في استجابتها باختلاف البيئات وبعضها في بيئات محددة. مقارنة فعالية طريقة تحليل معامل الارتداد الخطي وطريقة الاثر التجميعي الرئيسي والتفاعل المتراكم لتحليل اثر التفاعل بين الصنف والبيئة اوضحت الدراسة ان محور المكون الاول والثاني في طريقة الاثر التجميعي الرئيسي والتفاعل المتراكم فسر %56,7،%19,3  من قيمة تفاعل البيئة مع التركيب الوراثي اما معامل الارتداد قد فسر حوالي 21,9% من قيمة التفاعل بين البيئة والتركيب الوراثي  وعليه ، طريقة الاثر التجميعي الرئيسي والتفاعل المتراكم تفوقت علي طريقة تحليل معامل الارتداد الخطي وهي ذات كفاءة عالية في تقسيم مجموع مربعات الانحرافات. بناءً علي نماذج التحليل (Eberhard and Russel 1966) و Additive Main Effects  and  Multiplicative Interaction) AMMI) لتحديد ثبات الاداء معاً وجد أن السلالات ذات الإنتاجية العالية هي مقد( 1510 كجم/ هكتار) ، طابت (1299 كجم/هكتار)، ود أحمد (1471 كجم/ هكتار) ، زهرة القدمبلية ( 1428 كجم/هكتار) ، صفراء( 1410 كجم/هكتار) وتيترون(1323  كجم/هكتار) ذات انتاجية عالية وثابتة ويمكن زراعتها في جنوب القضارف والرهد والسلالات ود باكو( 1225 كجم/هكتار) ، فرهوده (  1252كجم/هكتار)، قشيش (1194 كجم/هكتار) وود فحل  (1230 كجم/ هكتار)  ذات انتاجية أقل ولكنها ثابتة نسبياً ويمكن زراعتها في شمال القضارف.